Study the effect of spraying of proline in the vegetative growth of the sun flower plant (Helianthus annuus L.) under different levels of water stress - Hameed Al- Da'mi, B. A. (Journal of Kerbala for Agricultural Sciences, 2017)
The study was carried out using plastic pots in the Department of Biology- College of Education for Pure Sciences / Karbala University during the growing season (2015-2016) to study the effect of the interaction between different levels of water stress and proline acid in some growth indicators of the sun flower plant, which included (plant height , number of leaves, Leaf area, dry matter content and dry weight of root system). Factional experiment within a completely randomized design (C.R.D.) with three replications was applied . The experiment included three concentrations of proline acid (0, 30 and 60) mg. L -1 and three levels of water stress (100%, 75%, 50%) of the field capacity. The experiment included 27 units (experimental unit). The results were statistically analyzed and the averages were measured using the least significant difference below the probability level of 0.05. The results showed that the added water level of 100% of the field capacity value gave the highest values ​​for the studied traits (plant height, number of leaves, leaf area, dry matter content and dry weight of root system). It was also sprayed with proline acid with a concentration of 60 mg. L -1 gave higher values for the above-mentioned traits. Meanwhile showed bilateral interactions between the levels of water stress and proline acid showed a various effect on the studied traits.